Clinical imaging of marrow adiposity. Issue 4 (July 2021) - Jarraya, Mohamed; Bredella, Miriam A.
Abstract : Research examining bone marrow adipose tissue (BMAT) has rapidly expanded during the last two decades, leading to advances in knowledge on the role of BMAT in the pathogenesis of bone loss and endocrine disorders. Clinical imaging has played a crucial role for the in vivo assessment of BMAT, allowing non-invasive quantification and evaluation of BMAT composition. In the present work, we review different imaging methods for assessing properties of BMAT. Our aim is to review conventional magnetic resonance imaging (MRI), water-fat imaging, and single-voxel proton magnetic resonance spectroscopy ( 1 H-MRS), as well as computed tomography (CT)-based techniques, including single energy and dual energy CT. We will also discuss the clinical applications of these methods in type 2 diabetes mellitus, obesity and anorexia nervosa.